Ulasan Literatur: Faktor-Faktor yang Mempengaruhi Adopsi Mobile Cloud Computing pada Mahasiswa - Nina Fadilah Najwa; Muhammad Ariful Furqon; Eki Saputra (Ultimatics : Jurnal Teknik Informatika, 2020)
Mobile Cloud Computing provides cloud storage services to users inside a cloud. This study focuses on the factors that influence the adoption of mobile cloud storage usage in the higher education. The research methods used in this study include: (1) problem formulation; (2) literature search; and (3) formulation of factors for adopting mobile cloud computing (4) validation and reliability test. The results obtained is a conceptual model that can be tested empirically. The main five factors are: (1) knowledge sharing variables; (2) Perceived usefulness variable (3) trust variable; (4) the attitude towards variable; and (5) the variable of behavioral intention of use. Each variable formulated in the conceptual model will be developed into items that are measurement indicators. The research contribution is in the form of a research model that is useful for empirical research on the factors of adoption of the use of Mobile Cloud Computing in the education sector.